Ethical aspects of the use of social networks during the employment process - Branislav Sančanin (Trendovi u Poslovanju)
Social networks have significantly contributed to the relativization of the boundaries between private life and the business sphere, which has enabled employers to more easily and quickly obtain relevant data during the employment process, while avoiding contact with the candidates. Employers violate the privacy of potential candidates by obtaining data in this manner without making prior notification and receiving consent, which opens up a whole range of complex ethical and legal issues, especially in the light of the large number of fake profiles and pages on social networks. On the other hand, candidates applying for a vacant position have the opportunity to get to know an organization's employers and employees in more detail, and to gather more information that can often be decisive when making the final decision on whether or not to send in a job application. Most employers today use social media during the process of collecting data on job candidates. Employers cite inappropriate photos, videos or information, followed by announcements pertaining to alcohol or drug consumption, as well as detected discriminatory comments, as the most common reasons for not hiring candidates after verification through social networks.